The Presence of the invasive Lionfish Pterois miles in the Mediterranean Sea - BARICHE, M.; TORRES, M.; AZZURRO, E. (Mediterranean Marine Science, 2013)
Here we report the occurrence of Pterois miles in the Mediterranean Sea, based on the capture of two specimens along the coast of Lebanon. Previously, only one record of the species from the Mediterranean Sea had been documented. The new records highlight the arrival of new propagules of P. miles, more than two decades later, hinting to a future potential invasion of the Mediterranean Sea.